Assessment of educational technology in lactation physiology by health students - Daiani Oliveira Cherubim; Polyana de Lima Ribeiro; Tassiane Ferreira Langendorf; Cristiane Cardoso de Paula; Stela Maris de Mello Padoin (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to assess the suitability, facilitators, and barriers of using a video clip for teaching lactation physiology to health students. Methods: a cross-sectional study was conducted with online data collection at a higher education institution, using the Assistive Technology Assessment Instrument and open-ended questions. The sample consisted of 88 students. Results: the video clip was deemed suitable in all attributes. Facilitators identified included attractiveness, musicality, and ease of access. Barriers noted were the music's speed and the necessity for prior knowledge. The video clip achieved adequate scores for interactivity (1.71), purpose (1.77), relevance (1.64), and clarity (1.77). The overall average of the attributes was 1.72. Conclusions: the video clip can serve as an effective learning strategy to enhance hybrid education, potentially contributing to the promotion and support of breastfeeding. However, some barriers underscore the importance of prior knowledge for a complete understanding of the content.